Performance of two interferon-gamma release assays for tuberculosis infection screening in Kawasaki children before immunosuppressive therapy - Chen, Hao; Zheng, Huiwen; Cui, Lang; Xiao, Jing; Li, Feina; Wang, Yonghong; Guo, Yajie; Chen, Yuying; Yuan, Yue; Shen, Chen (Frontiers in Pediatrics, 2023)
Objective We aimed to compare QuantiFERON-TB Gold In-Tube (QFT-GIT) and X.DOT-TB for screening latent tuberculosis infection (LTBI) in kawasaki patients, and to identify the risk factors associated with indeterminate IGRA results. Methods We conducted a retrospective study on children with KD, who were screened for mycobacterium tuberculosis (Mtb) infection by either ELISA-based QFT-GIT or ELISPOT-based X.DOT-TB tests, admitted in Department of Cardiology, Beijing Children's Hospital from July 2019 to April 2022. Results A total of 1327 cases were included. Among them, 932 cases were tested by QFT-GIT and 395 cases by X.DOT-TB. The positive rate of children was 0.1% and 0.2%, and the indeterminate rate was 68.2% and 6.1% for QFT-GIT and X.DOT-TB, respectively. Patients with hypoproteinemia had a higher risk of indeterminate X.DOT-TB result. Female, critical ill, shock or hypoproteinemia presented statistically significant associations with an increased risk of indeterminate QFT-GIT result. High-dose of IVIG inhibited the release of IFN-γ by more than 90%, which might account for the high indeterminate incidence. Conclusion It is recommended to perform X.DOT-TB rather than QFT-GIT to screen LTBI in patients with high level of the mitogen that can inhibit IFN-γ release. For KD children with positive IGRA results, it has a higher risk of activation TB infection when treated with immunosuppressive therapy in the future. Children with KD aged <5 years old had higher frequency of indeterminate IGRA results.